Human Beta-defensin-1 and Periodontal Disease: The Past, Present, and Future - Benso Sulijaya; Sri Lelyati C Masulili; Elza Ibrahim Auerkari (Indonesian Dental Association, 2021)
Human beta-defensin-1 (HBD-1), a peptide released by the immune system, has been investigated for its association with periodontal disease. Several studies have found positive findings of its expression related to disease progression, whereas others have reported some tendencies. This review highlights studies associated with HBD-1 and periodontal disease in both primary and clinical investigations, as well as the underlying mechanism and discusses further research possibilities for HBD-1. HBD-1 acts as an innate immune apparatus and mediating the adaptive immune system; therefore, its role in the pathogenesis of a periodontal disease is indisputable. HBD-1 is mainly expressed in the oral stratified epithelium and sulcular epithelium, where the barrier junction properties (e.g., E-cadherin and Î²-catenin in the adherent junction) of the gingival epithelial cells serve as the first line of defense against periodontal infection. The HBD-1-reinforced epithelium therefore provides both a mechanical and a chemical barrier action. Critical issues that arise in the gingival epithelium can therefore be alleviated by modulation of HBD-1 production to enhance its protective function. The antimicrobial, anti-inflammatory, and wound healing properties of HBD-1 support its use as a promising clinical treatment strategy.